ANALISIS HASIL PRODUK ALAT PERTANIAN MENGGUNAKAN TUNGKU PACK KABURISING DENGAN TUNGKU KONVENSIONAL - Samsudi Raharjo (Universitas Muhammadiyah Semarang, 2007)
This research was conducted to improve the model of Black Smith’s fireplace from the small scale industries of agricultural tools (hoe, sickle, cutting knife, crafting tools). This sector remains an important one in Indonesian economy and man power. The area of research covers Semarang Municipality, Semarang Regency and Jepara Regency, used a parameter beyond the area of Ceper, Klaten Regency and Tegal that are well-known as the basis of small scale metal industries in Central Java. From their roles in opening employment, the small scale industries are often referred to as the venue of cheap and effective entrepreneurship training. Indonesia has significant capital to become self-reliance nation which can produce various products, however, we are too busy consuming products imported from other countries that are considered to have many advantages if compared with the local ones, in spite of more expensive price. The method applied in this research was experimental testing, technological design, design trial, the analysis of differential testing and regression method. The testing to check the improvement quality resulted from solid carburetion is conducted through the hardness testing, in which the hardness value increases on the surfaces where solid carburetion was conducted. The research showed that there was a significant difference in term of hardness of resulted products between the conventional fireplace and the fireplace model designed with solid carburetion using coconut shell as fuel. The improvement of fireplace model is expected to: (1) change work habit to the safer one, (2) improve the quality of agricultural tools, and (3) socialize the design of fireplace with solid carburetion using the coconut shell as fuel to the black smiths in Central Java. Kata Kunci : Fireplace, Tool and Quality